PENGARUH KECERDASAN EMOSIONAL DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI (Studi pada Mahasiswa Akuntansi Program S1 Universitas Brawijaya) - Jayadi, Ahmad Rizal; Purwanti, Lilik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to examine impact of emotional intelligence that is measured by self understanding, self control, motivation, empathy, and social ability, and learning behavior that is measured by aspects of the habit following the lesson, the habit of reading books, visiting libraries, and habits for exams whereas accounting understanding was measured by score of accounting subjects. Research sample is 80 respondents. Data analysis method is multiple regression. Result of examination indicates that hypothesis 1 which stated that emotional intelligence by self understanding, self control, motivation, empathy, and social ability significantly influence the interest of accounting understanding. Hypothesis 2 which stated that learning behavior measured by aspects of the habit following the lesson, the habit of reading books, visiting libraries, and habits for exams significantly influence the interest of accounting understanding. Hypothesis 3 which stated that emotional intelligence and learning behavior in a together influence the interest of accounting understanding. Keywords: Emotional Intelligence, Learning Behavior, Accounting Understanding